The Tarbiyah Movement: Why People Join This Indonesian Contemporary Islamic Movement - Salman, Salman (Studia Islamika, 2006)
This study seeks to explain the reasons behind people's participation in the Tarbiyah Movement in Indonesia. Although this movement has had phenomenal political and social achievements, it appears to be exclusive in the sense that it is dominated by a certain type of Indonesian Muslim. That is, as observed by the likes of Bahtiar Effendy, the core participants of the Tarbiyah Movement tend to be Muslims who are young and well-educated. This does not mean, however, that all those who fit this description join the Tarbiyah Movement. In fact, there are many of those with the same characteristics who not only do not participate in the movement but even oppose of it.DOI: 10.15408/sdi.v13i2.566